COOPERAÇÃO JURIDICA INTERNACIONAL EM MATÉRIA PENAL E EQUIPES CONJUNTAS DE INVESTIGAÇÃO: UM MECANISMO NO COMBATE EFICIENTE AO CRIME ORGANIZADO TRANSNACIONAL. - Guilherme Guimarães Farias (2022)
The Federal Constitution of 1988 (BRASIL, 1988) in an innovative way provides as a principle in its international relations, the cooperation between peoples for the progress of humanity, as well as the economic, political, social and cultural integration of the peoples of Latin America, aiming at the formation of a Latin American community of nations. Thus, the Constitution guarantees the integration and openness of the State to international cooperation, favoring good faith, the security of international pacts and the effective legal certainty, so necessary in a context of increasing transnational crime a deleterious fruit of the phenomenon of globalization. The objective of this work is to analyze the Joint Investigation Teams as a modern instrument of International Legal Cooperation in criminal matters, providing both an efficient criminal prosecution and respect for the fundamental guarantees of the investigated. For the development of this work, descriptive, explanatory and exploratory research was used, with the use of a deductive approach and use of articles, doctrines and legislation, mainly international. The Joint Investigation Teams emerge as important tools for ensuring access to justice, legal certainty and an effective scope of transnational judicial protection. Based on this cooperative spirit, Brazil promulgated the main multilateral conventions to combat crime, implementing public policies and efficient legislation to persuade organized crime. For this, it is necessary a new look at the concept of national sovereignty, in order to seek an integration of wills between countries that seeks the legitimation of acts practiced beyond their borders, overcoming the current problem of production, exchange and introduction of evidence obtained in territories different from the jurisdiction competent for the trial. At the regional level, Mercosur implemented the Framework Cooperation Agreement between Mercosur States Parties and Associated States for the Creation of Joint Investigation Teams, promulgated in Brazil in 2020, which made it possible, even timidly, to form research teams composed of agents from two or more countries to investigate crimes perpetrated in various national territories, always respecting the fundamental rights and guarantees, which underpin the universal standard of human rights.